2018
DOI: 10.3390/ma11122588
|View full text |Cite
|
Sign up to set email alerts
|

PLA- and PLA/PLGA-Emulsion Composite Biomaterial Sheets for the Controllable Sustained Release of Hydrophilic Compounds

Abstract: In the present study, by spin-coating a solution containing w/o (water-in-oil) emulsions and hydrophobic polymers, we obtained sheets possessing uniformly dispersed w/o emulsions. We performed release experiments for more than 100 days and clarified the effects of the number of layers, the sheet-forming polymers (polylactide (PLA), poly(lactic-co-glycolic acid (PLGA)), the ratio of organic solvent to water, and the composition of block copolymers on the release properties of the sheets. For a variety of sheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…This may be due to the addition of nHA. It is well known that PLA is a hydrophobic molecule [73], and the addition of nHA enhances certain hydrophilicity. For fat-soluble antibiotics, PLA may form a chemical bond with it, resulting in good adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the addition of nHA. It is well known that PLA is a hydrophobic molecule [73], and the addition of nHA enhances certain hydrophilicity. For fat-soluble antibiotics, PLA may form a chemical bond with it, resulting in good adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Different materials designs include fibers, microparticles, nanoparticles, films, and porous scaffolds [3,4,5], and poly (lactic acid) and its copolymers with poly (glycolic acid). These are among the most used polyesters in medicine [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have found that hydrophilicity is an advantage for bioactive materials. It can improve cell attachment, spreading, and proliferation [29,30]. The water contact angle results of various polymeric substrates with different treatments are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is extremely interesting to monitor eventual alterations in surface morphology, as they are likely to considerably affect cell growth. In order to maintain a surface with a high level of hydrophilicity and functionality at the surface, subsequent modification by grafting of organic acid onto a plasma treated polymer was carried out [28,29,30,31]. Plasma polymerization has consequently proven highly successful as a means of developing functional interfaces for cell culture [27,32,33].…”
Section: Introductionmentioning
confidence: 99%